2009
DOI: 10.1136/bmj.b1326
|View full text |Cite
|
Sign up to set email alerts
|

Meeting information needs of patients with incurable progressive disease and their families in South Africa and Uganda: multicentre qualitative study

Abstract: Objectives To explore the information needs of patients with progressive, life limiting disease and their family caregivers in South Africa and Uganda and to inform clinical practice and policy in this emerging field.Design Semistructured qualitative interview study.Setting Four palliative care services in South Africa and one in Uganda, covering rural, urban, and peri-urban locations.Participants 90 patients and 38 family caregivers enrolled in palliative care services; 28 patients had cancer, 61 had HIV infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 45 publications
2
87
0
6
Order By: Relevance
“…Research on the relationship between patients' understanding of pain and reported pain intensity, conducted in developed countries and with patients with chronic lower back pain and chronic fatigue syndrome, has found that basic education about pain can reduce pain intensity and catastrophic thinking about pain. 16,17 Although one study has investigated general information needs of patients in pain in South Africa and Uganda, 18 we are unaware of any research on patient understanding of pain in resource poor settings. This is an important area for further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…Research on the relationship between patients' understanding of pain and reported pain intensity, conducted in developed countries and with patients with chronic lower back pain and chronic fatigue syndrome, has found that basic education about pain can reduce pain intensity and catastrophic thinking about pain. 16,17 Although one study has investigated general information needs of patients in pain in South Africa and Uganda, 18 we are unaware of any research on patient understanding of pain in resource poor settings. This is an important area for further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…Further studies have identified advanced care needs in Uganda of communication and information,11 spiritual care,12 13 and for amelioration of pain and psychological distress 14. However, very little is known about the proportion of hospital populations with life-limiting disease, who therefore may have palliative care needs.…”
Section: Introductionmentioning
confidence: 99%
“…4 Although some quantitative research has been done in the field of palliative care in Uganda, only a few studies have taken a qualitative approach. [5][6][7][8] None of these focus on the work of nurses. For that reason, among others, more research is needed about the palliative care nurse specialist (PCNS) in Uganda. Studying the role of the PCNS in Uganda could potentially contribute to the body of knowledge from which other countries might learn.…”
Section: Introductionmentioning
confidence: 99%
“…This is possibly a result of the general ignorance about cancer. Selman et al 30 found that patients and caregivers lack information about their condition, and their informational needs are not being attended.…”
mentioning
confidence: 99%